Analisis Dampak Pergantian Kurikulum 2013 Ke Kurikulum Merdeka Terhadap Pembelajaran Di Sekolah Dasar - Muhardini, Sintayana; Sari, Nursina; Amelia, Sherly Dwi; Rahman, Nanang; Muhdar, Syafruddin; Bilal, Arpan Islami; Handayani, Monika (Jurnal Ilmiah Telaah, 2025)
Modifications in the curriculum of education signify advancements in science and technology. The Merdeka curriculum is an initiative aimed at addressing contemporary demands and technological integration, affecting education across multiple levels. This study seeks to evaluate the transition to the independent curriculum from the 2013 curriculum in primary schools, focusing on its implementation, challenges, impacts, and potential solutions. This research employs a descriptive qualitative methodology. The findings of this study indicate that the independent curriculum is executed in phases in accordance with governmental directions. The process of transitioning the independent curriculum from the 2013 curriculum has three transitional stages: freedom to learn, share, and change. The main obstacle is teacher adaptation to a new, more flexible approach. In addition, limited facilities and infrastructure, such as the availability of learning books, digital devices, and technological literacy, are a challenge. The positive effects are that student participation in the learning process becomes more active, creative, and oriented in each task. In terms of administration, the workload becomes lighter. Solutions for Handling the Obstacles of the 2013 Curriculum Transition to the Independent Curriculum in Elementary Schools include providing intensive assistance to teachers, optimizing training, and conducting regular evaluations to see what still needs improvement.